Immunotherapy for IgE-mediated wheat allergy - Pacharn, P. (Hum Vaccin Immunother, 2017)
Among various routes of immunotherapy for food allergy, oral immunotherapy (OIT) appears to have a promising result due to its ability to modify abnormal immunologic mechanism of IgE-mediated food allergy. Other methods for immunomodulation such as sublingual (SLIT) or epicutaneous (EPIT) immunotherapy which carry lower rates of systemic reactions, may have less efficacy. Wheat has recently been recognized as a more common cause of food-induced anaphylaxis than previously recognized, especially among young children, around the world. In wheat allergic patients, avoidance recommended as standard recommendation is not easy to follow, because wheat has been used as a common constituents in various kinds of consumed foods in every day's life. Therefore, wheat OIT may be considered as an alternative treatments of those in which wheat avoidance is not sufficient to avert frequent events of anaphylaxis resulting from inadvertent exposure to small amount of wheat among this population. Currently, only few clinical trials about wheat OIT are available. In this review, we discuss available protocols of wheat OIT, initial starting dose, maintenance dose, and the strategies to minimize the side effects during the treatment.